INFORMATION PROCESSING DEVICE, INFORMATION PROCESSING METHOD, AND PROGRAM - IZUMI, Akihiko; HARA, Masahiro (2019)
An information processing device according to one embodiment of the present invention is provided with: an acquisition unit; a setting unit; and a process execution unit. The acquisition unit acquires the reliability of modal authentication which is executed for a user. The setting unit sets a reliability threshold value on the basis of a request made by the user. The process execution unit suspends execution of a process corresponding to the request made by the user until the acquired reliability of modal authentication becomes greater than the set reliability threshold value. Un dispositif de traitement d'informations selon un mode de réalisation de la présente invention comprend : une unité d'acquisition ; une unité de configuration ; et une unité d'exécution de processus. L'unité d'acquisition acquiert la fiabilité d'authentification modale qui est exécutée pour un utilisateur. L'unité de configuration définit une valeur de seuil de fiabilité en fonction d'une demande effectuée par l'utilisateur. L'unité d'exécution de processus suspend l'exécution d'un processus correspondant à la demande effectuée par l'utilisateur jusqu'à ce que la fiabilité acquise de l'authentification modale devienne supérieure à la valeur de seuil de fiabilité définie. 本技術の一形態に係る情報処理装置は、取得部と、設定部と、処理実行部とを具備する。前記取得部は、ユーザに対して実行されるモーダル認証の信頼度を取得する。前記設定部は、前記ユーザの依頼した要求に基づいて信頼度閾値を設定する。前記処理実行部は、前記取得されたモーダル認証の信頼度が、前記設定された信頼度閾値より大きくなるまで、前記ユーザの要求に応じた処理の実行を保留する。